Neuroprotective efficacy of lifarizine (RS-87476) in a simplified rat survival model of 2 vessel occlusion. - McBean, D. E. (1995)
1. A new, modified rat two vessel occlusion model (with hypotension) was established and the neuroprotective efficacy of the novel agent lifarizine (RS-87476) was examined. 2. The two vessel occlusion model used in the study was a modification of the model described in the literature, whereby we have obviated the need to use a muscle relaxant and intubate the trachea to provide ventilatory support by providing a tight fitting face mask attached to the ventilator. Furthermore, the need to combine exsanguination and additional pharmacological means of inducing the mandatory hypotension (50 mmHg), required to decrease brain blood perfusion pressure, has been removed by simply manipulating the concentration of the already present halothane anaesthetic. 3. The appropriate level of hypotension having been reached, microvascular clips were applied to bilaterally occlude the common carotid arteries for 12 min. This resulted in a loss of the cortical EEG activity. Local cerebral blood flow was measured 6 min into the occlusion period, using the fully quantitative [14C]-iodoantipyrine autoradiographic technique, in a separate group of rats (n = 5). This illustrated the lack of any blood flow, in the areas under study, during the period when there was an isoelectric cortical EEG pattern. 4. The high grade global ischaemic lesion which occurred gave quantifiable neuronal damage in several vulnerable regions of the brain, namely, the hippocampal CA1 sub-field, cortex, thalamus, striatum, and cerebellar brain stem (Purkinje cells). 5. Following the global ischaemic insult the rats were allowed to recover for 72 h before assessment of the damage, during which time one group of rats (n = 11) received 100 micrograms kg-1 lifarizine i.a. 5 min post-occlusion, 500 micrograms kg-1 lifarizine i.p. 15 min post-occlusion, and 500 micrograms kg-1 lifarizine i.p. twice daily for 72 h. A second group of rats (n = 12) was treated with appropriate volumes of vehicle (0.4 ml kg-1 i.a. and 2 ml kg-1 i.p.) at identical time points. 6. Histopathological damage was assessed, from cresyl violet and haematoxyline/eosin stained sections, using a scoring system of 0-6 (no damage-complete neuronal death). The dosing regimen of lifarizine gave reduced damage in the hippocampal CA1 sub-field (4.1 +/- 0.3 to 2.8 +/- 0.6) and striatum (1.7 +/- 0.3 to 1.2 +/- 0.3) and significant neuroprotection in the anterior cortex (2.0 +/- 0.2 to 1.2 +/- 0.2; p < 0.05), thalamus (1.5 +/- 0.2 to 0.8 +/- 0.2; p < 0.01), posterior cortex (1.5 +/- 0.2 to 1.0 +/- 0.2; p < 0.05) and cerebellar brain stem (0.9 +/- 0.2 to 0.4 +/- 0.1; p < 0.01). The overall mean brain score was significantly reduced (from 1.5 +/- 0.1 to 0.9 +/- 0.2). 7. These data show that the newly modified 2 vessel occlusion model produced a quantifiable level of ischaemic damage and that the novel agent lifarizine is neuroprotective in the model.